Civil engineering as applied in construction - Vernon-Harcourt, Leveson Francis, 1839-1907 (Longmans, Green and Co., 1902)
This volume brings together a concise treatment of the various branches of constructive civil engineering.
Keywords: Civil engineering.; Building.; elektronické knihy; electronic books